2015
DOI: 10.4049/jimmunol.1401624
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil IL-1β Processing Induced by Pneumolysin Is Mediated by the NLRP3/ASC Inflammasome and Caspase-1 Activation and Is Dependent on K+ Efflux

Abstract: Although neutrophils are the most abundant cells in acute infection and inflammation, relatively little attention has been paid to their role in inflammasome formation and IL-1β processing. In the current study, we investigated the mechanism by which neutrophils process IL-1β in response to Streptococcus pneumoniae. Using a murine model of S. pneumoniae corneal infection, we demonstrated a requirement for IL-1β in bacterial clearance, and showed that NLRP3, ASC and caspase-1 are essential for IL-1β production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
226
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(243 citation statements)
references
References 59 publications
15
226
2
Order By: Relevance
“…Several studies provide evidence that in neutrophils, the relationship between gene transcription and translation is far from linear. (42,45,46) Notably, we did not detect p65 and IkBβ proteins in the nuclear fraction. This observation is in line with the finding that the IκBα-NF-κB complex shuttles between cytoplasm and nucleus while the IκBβ-NF-κB complex is cytosolic and does not undergo shuttling at all.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies provide evidence that in neutrophils, the relationship between gene transcription and translation is far from linear. (42,45,46) Notably, we did not detect p65 and IkBβ proteins in the nuclear fraction. This observation is in line with the finding that the IκBα-NF-κB complex shuttles between cytoplasm and nucleus while the IκBβ-NF-κB complex is cytosolic and does not undergo shuttling at all.…”
Section: Discussionmentioning
confidence: 81%
“…(11,(39)(40)(41) This latter observation prompted us to investigate the effect of currently used preparations of A1AT in treating humans on processing secretion of active IL-1β in LPS-activated human blood neutrophils in vitro. It is important to point out that a major source of IL-1β (39,42,43); moreover, neutrophil-derived IL-1β mediates further neutrophil recruitment and activation. Synthesis of the IL-1β precursor is considered as a priming step, whereas intracellular cleavage of the IL-1β precursor and secretion of active IL-1β is a key step in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that PLO pore-forming activity is essential to induce inflammatory responses in vivo. PLY, another CDC, induces the upregulation of proinflammatory cytokines through numerous mechanisms, such as inducing cell necroptosis [29] and pyroptosis [30], promoting platelet activation and platelet–neutrophil interactions [31], initiating the transcription of genes of proinflammatory cytokines [32], and activating inflammasomes to promote the maturation of certain proinflammatory cytokines by changing the intracellular ion concentration [22]. Most of these events are related to the pore-forming activity of PLY.…”
Section: Discussionmentioning
confidence: 99%
“…PLY, one of the most extensively studied CDCs, exhibits several biological properties, such as activation of the complement system [20], platelets [21], and NLR family pyrin domain containing protein 3 (NLRP3) inflammasome [22] or stimulation of pattern recognition receptors (PRRs) [23,24]. Studies indicated that the pore-forming activity and pathogen-associated molecular pattern (PAMP) activity of the toxin form the foundation for most of the previously mentioned biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PLY-dependent secretion of these cytokines could contribute to both host protection and pathogenesis during S. pneumoniae infection. To understand the mechanism of how these cytokine responses are induced in a PLY-dependent manner, we and others previously reported that in S. pneumoniae-infected macrophages, the maturation and secretion of IL-1␤ and IL-18 are dependent on the activation of caspase-1, which is induced by the assembly of inflammasomes, including the absent in melanoma 2 (AIM2) and NLR family pyrin domain-containing 3 (NLRP3) inflammasomes (9)(10)(11)19).…”
mentioning
confidence: 99%